Adaptation of method of coulometric titration to determin antioxidant activity of digister and dietary additions - Євлаш, Вікторія Владленівна; Михайленко, Володимир Григорович; Акмен, Вікторія Олександрівна (Eastern-European Journal of Enterprise Technologies, 2011)
This work shows short analysis of the most known methods of determination of antioxidant activity and offers the method of adaptation of method of coulometric titration to determin antioxidant activity of digister and new dietary additions of «Redgem», «Kalgem», «Fytogem» as in filtered so in unfiltered water extracts